Infant Care In The Agricultural Community Of Ethnic Blambangan Banyuwangi - Rasni Sihaloho, Hanny; Kurdi, Fahrudin; Asih Larasati, Niken; Susanto, Tantut (Poltekkes Kemenkes Surakarta, 2024)
Background: Data on infant mortality in Banyuwangi shows an increase in the last five years; data on infant breastfeeding has not been achieved either; while Indonesia's history of the Blambangan people, Banyuwangi, is recorded as healthy, strong, and thick with culture, known to be skilled in care, including baby care. Research is needed to find out the culture of infant care in the Blambanga ethnic community so that a good infant care culture can be strengthened to improve health. Methods: The research used an ethnographic research design, with a sample size of 39 people; data were collected through FGDs, in-depth interviews, participatory observation, and documentation and analysed thematically using ethnographic and Colaizzi analysis. Several online applications were used in data processing and diagramming the results, and ethical principles were applied. Results: The themes identified in the culture of infant care in the Blambangan community are cutting the umbilical cord, infant massage, the role of baby shamans, the use of plants as therapy, celebrations for babies, swaddling babies, feeding babies under six months, beliefs related to infant care, and environmental modifications when having children. Some cultures need to be reinforced. Conclusion: The culture of good breastfeeding in the Osing Banyuwangi community, recorded in Indonesian history, must be reconstructed. The culture of good infant care needs to be reinforced to achieve better health, and this research needs to be developed to reconstruct the culture of infant care in the Osing Banyuwangi community.